The social, political and historical contours of deportation - Anderson, Bridget (Sociologist); Gibney, Matthew J.; Paoletti, Emanuela, 1980- (Immigrants and minorities, politics and policy., 2013)
In recent years states across the world have boosted their legal and institutional capacity to deport noncitizens residing on their territory, including failed asylum seekers, "illegal" migrants, and convicted criminals. Scholars have analyzed this development primarily through the lens of immigration control. Deportation has been viewed as one amongst a range of measures designed to control entrance, distinguished primarily by the fact that it is exercised inside the territory of the state. But deportation also has broader social and political effects. It provides a powerful way through which.